2016
DOI: 10.18271/ria.2016.203
|View full text |Cite
|
Sign up to set email alerts
|

Viabilidad in vitro e in vivo de los espermatozoides congelados/descongelados del conducto deferente de Alpacas (vicugna pacos)

Abstract: KEY WORDS:Viabilidad in vitro e in vivo de los espermatozoides congelados/descongelados del conducto deferente de alpacas (Vicugna pacos)Viability in vitro and invivo of sperm frozen/thawed from alpaca (Vicugna pacos) vas deferens El objetivo del presente estudio fue evaluar la viabilidad in-vitro e in-vivo de los espermatozoides procedente de los conductos deferentes de alpacas. Se utilizaron 2 reproductores como donadores de espermatozoides con desviación del conducto deferente. Los espermatozoides colectado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
1
4
2
Order By: Relevance
“…This study collected alpaca semen by postcoital aspiration, and an extender based on Tris-egg yolk was used, obtaining an average range of refrigerated sperm motility from 57.3% to 61.5%. On the other hand, Pérez Durand et al (2016) reported motility values somewhat lower than those observed in our study, after alpaca sperm was cooled to 5°C in a period of 3 h (mean ranging from 48.3 to 52.6%). Even though they use the commercial extender Triladyl®, the authors collected samples from the deviation of the vas deferens.…”
Section: Ta B L Econtrasting
confidence: 91%
See 2 more Smart Citations
“…This study collected alpaca semen by postcoital aspiration, and an extender based on Tris-egg yolk was used, obtaining an average range of refrigerated sperm motility from 57.3% to 61.5%. On the other hand, Pérez Durand et al (2016) reported motility values somewhat lower than those observed in our study, after alpaca sperm was cooled to 5°C in a period of 3 h (mean ranging from 48.3 to 52.6%). Even though they use the commercial extender Triladyl®, the authors collected samples from the deviation of the vas deferens.…”
Section: Ta B L Econtrasting
confidence: 91%
“…Among the multiple available commercial options for semen extenders, several of them have been used to freeze alpaca sperm, although none of them are SAC-specific (Green/clear camel buffer; Biladyl® A and B;Triladyl®;, and with low pregnancy rates (0% to 25%) after AI implementation (Morton et al, 2010;Pérez Durand et al, 2016;Stuart et al, 2019;Vaughan et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This option is too severe for the animal and does not allow repeated sampling. The alternative technique used in this study is the best option for removing both limitations (Gómez‐Quispe, Pérez, & Machaca, ; Pérez Durand, Zevallos Aragón, & Pérez Guerra, ).…”
Section: Discussionmentioning
confidence: 99%
“…There are previous studies focused on alpaca spermatozoa without seminal plasma, which were collected post mortem from the epididymis (Choez et al, ) and with the same procedure used in this work (Gómez‐Quispe et al, ; Pérez Durand et al, ; Perez et al, ). Yet, the subjective analysis of total motility showed higher values than our results.…”
Section: Discussionmentioning
confidence: 99%